The Impact of Cognitive Heterogeneity on the Behavioral Integration of the R&D Team: The Perspective of Conflict Management - Hongtao Xie; Yun Song; Chaoxun Cai; Junwei Zheng (Discrete Dynamics in Nature and Society)
The impact of team heterogeneity on team effectiveness has received extensive attention. The paper aims to explore the mechanism of the effect of cognitive heterogeneity on behavioral integration in R&D teams. Based on the IPO theory, this study proposed six hypotheses about how cognitive heterogeneity directly and indirectly (via team conflict and conflict management) affect behavioral integration in R&D teams. Using data collected from 383 R&D teams in 326 high-tech enterprises in China, we investigated whether the dimensions of team conflict mediate the relationship between cognitive heterogeneity and behavioral integration and whether the dimensions of conflict management regulate the impact of cognitive heterogeneity on behavioral integration. The results show the following: (1) cognitive heterogeneity has a significant negative impact on the behavioral integration of R&D teams. Task conflict and relationship conflict fully mediate the relationship between cognitive heterogeneity and behavioral integration. (2) Cooperative conflict management positively moderates the impact of cognitive heterogeneity on task conflict and the impact of task conflict on team behavioral integration. (3) Avoidance conflict management reversely adjusts the positive impact of cognitive heterogeneity on task conflict and relationship conflict and the negative impact of relationship conflict on team behavioral integration. The research results can provide theoretical guidance to improve the process management of cognitive heterogeneity R&D teams.